PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN PADA PT TRISULA INTERNASIONAL TBK DAN PT PAN BROTHERS TBK - Mukmainah, Nafisa Al Sulis; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of Return On Assets (ROA) and Debt to Equity Ratio (DER) on firm value at PT Trisula International Tbk and PT Pan Brothers Tbk. This research uses an associative method with a quantitative approach. The type of data used is secondary data obtained from the companies’ financial statements during the research period (for example, 2015–2024). The data analysis techniques include classical assumption tests, multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²). The results show that Return On Assets (ROA) has a positive effect on firm value, while Debt to Equity Ratio (DER) has a negative effect on firm value. Simultaneously, ROA and DER have a significant effect on firm value in both companies studied.